Correcting Network Failures: The Evolution of US Innovation Policy in the Wind and Advanced Battery Industries. (1st October 2013) - Keller, Matthew R; Negoita, Marian
Abstract : Innovation and industrial policy debates typically focus on appropriate government responses to market and bureaucratic failures. However, recent research has suggested that in an era of decentralized, "network" production, effective governmental approaches to innovation policy should also consider "network failures" a central obstacle to innovative dynamism. We utilize the network failure concept to analyse past efforts of the United States (US) Government to stimulate innovation in the wind and advanced battery industries, and place ineffectual US efforts to galvanize these fields alongside historically more successful approaches in Denmark and Japan, respectively. The case analysis underscores the relevance of network failures to ineffective US attempts to stimulate technological dynamism, and suggests the importance of both general policy frameworks and case-specific "relational work" in forging or inhibiting industrial collaborations. Finally, we draw on recent data to suggest that though US policy justifications typically remain rooted in market and bureaucratic-centric languages, recent programs have often tacitly turned toward multi-faceted strategies to seed and support complex innovation networks.